Metode Simple Additive Weighting Dalam Seleksi Penerimaan Beasiswa Pada Sekolah Madrasah Ibtidaiyah Al Huda Jakarta Timur - Ramadhan, Muhammad Rifki; Respati, Arya Nandian; Syamsah, Bakri; Mukhayaroh, Anna (Journal of Students‘ Research in Computer Science, 2021)
Educational institutions, especially Madrasah Ibtidaiyah, many scholarships are offered to prospective students, scholarships are also given to prospective students at Madrasah Ibtidaiyah Al Huda, East Jakarta, namely in the form of superior scholarships, several problems that often occur, for example the selection process is not accurate due to the large number of applicants who must register. according to the existing criteria, so that the selection process requires accuracy and time so this is not effective. Decision support applications are a way of dealing with the problem of determining scholarships at the Madrasah Ibtidaiyah. This application uses Simple Additive Weighing (SAW), chosen because this method determines the weight of each predetermined criterion then proceeds with the normalization process and continues with the ranking process to select the best alternative. The results of this study are a decision support system in the classification of scholarship recipients using the Simple Additive Weighting (SAW) method at Madrasah Ibtidaiyah Al Huda, East Jakarta based on a website with the results of the selected criteria C1 Academic Achievement, C2 Non-Academic Achievement, C3 Report Value, C4 Personality, C5 Parent's Dependent, C6 Parent's Income. Based on the results of research from the application of a decision support system in classifying scholarship recipients using the Simple Additive Weighting (SAW) method, it was successful so that it could be seen which students deserved the scholarship. This application makes it easier for Madrasah Ibtidaiyah in the new student admissions section to determine scholarship recipients according to existing criteria, faster and on target as expected compared to the previous system.